Asia Africa's Impact on Middle East's Specialty Coffee Community - Maspul, Kurniawan Arif (Indonesian Journal Publisher, 2024)
In an era when work entails accomplishment, personal progress, financial security, social connections, and finding meaning, the specialty coffee sector has become a magnet for experts from Asia and Africa looking to offer their skills to the Middle East's coffee value chain. This engrossing study dives into the motivations and preferences of labor from different regions, offering light on the unique dynamics that entice people to this particular sector and geographical context. The article investigates the cultural interchange, skill development opportunities, and career progression that attract workers to the Middle East's specialty coffee industry using prominent ideas such as the Pull-Push Theory, Resource-Based View Theory, and Cultural Diversity Theory. The findings not only demonstrate the transforming potential of work, but they also give critical insights for industry stakeholders, governments, and scholars interested in maintaining a thriving and inclusive coffee ecosystem in the region and beyond.